Location and pain prevalence among Croatian male taekwondo competitors - Miletic, A.; Cular, D.; Ivancev, V.; Mandic Jelaska, P. (Acta Kinesiologica, 2018)
The aim of this study was to identify characteristic pain prevalence in Croatian taekwondo athletes in order to indirectly decrease the number of injuries and organize a safer training process. The subject sample of 58 taekwondo athletes with internationalcompetitive experience was divided into four subsamples according to their body weight and competition category. Self-Estimated Functional Inability because of Pain questionnaire was used for data collection and neck, shoulders, elbows, upper arms, forearms, wrists, fingers, upper back, lower back, hips, thighs (front), thighs (back), knees, shins, calves, ankles/feet, and toes regions were analysed in accordance with the aim of the research. The most common pain reported by Croatian TKD athletes in total was in the knees (39.6%), lower back (31%), thighs/back (29.3%), ankles/feet (27.6%), and shoulders (20.7%) region. Early detection of lower intensity of pain can help in preventing the occurrence of injuries as well as improve professional guidance and appropriate safety requirements for taekwondo athletes.